Abdul Karim Jamak dan pemikirannya tentang konsep ketuhanan / Ahmad Zuhdi - Ahmad, Zuhdi (2017)
As a scholar in Kerinci District, Abdul Karim Jamak's thinking needs to be examined in the middle of society, as previously the teachings of Islam taught to his students are seen and understood by the local community by stating that he developed deviant teachings. Of course, such views are not acceptable only to the truth of the teachings they convey. His students are not only from the general public, but also educators, government officials and lecturers, and others. People should see clearly what Abdul Karim Jamak teaches. Consequently, before the conclusions and decisions of the deviation, not a single flow of flow and the teachings developed by a group of scholars, both individually and collectively, need to carry out several approaches and various methods. The study, entitled 'Abdul Karim Jamak and His Thoughts on the Divine Concept', uses qualitative research methods through two approaches namely Historical approach and Islamic theory approach. His ultimate aim is to study and examine the biography of Abdul Karim Jamak and his Thoughts on the Divine Concept. Which in detail talks about, Nature of God, the concept of God's Action and Qada and qadar. With the objective of the study is to analyze and identify the history and life of Abdul Karim Jamak and to express the role of thinking on the direction of God's concept. The author chose this figure as the object of study as he was a prominent figure in Indonesia, then conducted a Comparative Analysis as a comparative research. In addition, it also regulates the views of Kerinci people who had previously thought that Abdul Karim Jamak taught misguided teachings. From research findings it can be seen that Abdul Karim Jamak is a famous scholar, who has fought with his missionary activities inviting the Muslim community in Kerinci to practice the teachings of Islam in accordance with the law of the Prophet Muhammad s.a.w. From the concept of his thinking about the Godhead. Abdul Karim Jamak follows the thinking of Asyā'irah, based on the Quran and the hadith of the Prophet. S.a.w His divine teachings that have been understood and practiced have implicated his students and the Muslim community of Kerinci even to the archipelago. Abdul Karim Jamak deserves the title of Kiyai Haji (Kh) after developing his concept of Islamic thought and the concept of Divine not contrary to the Qur'an and the hadith.